PENINGKATAN LITERASI PERENCANAAN KEUANGAN SYARIAH ANGGOTA KARANG TARUNA BAMBU LARANGAN AMPERA - Amalia, Alvien Nur; Listiani, Meydian; Putri, Natasya Adithia; Falihah, Amara; Damayanti, Putri (Al-Ihsan: Journal of Community Development in Islamic Studies, 2024)
The younger generation represents the future of the nation. They demonstrate considerable potential for growth and development. One such area of focus is the enhancement of financial literacy, particularly among younger demographics, which has the potential to foster a more financially aware and stable society. The youth organization Bambu Larangan Ampera is comprised of young people who act as both catalysts and role models for their peers. Most of these individuals adhere to the Syariahc faith; however, they demonstrate a lack of comprehension regarding financial planning, particularly in the context of Sharia-compliant financial planning. This is a significant consideration, as it can be a crucial element in financial planning, both in the short and long term. Accordingly, a needs assessment was conducted as part of the community service programme, which identified a need to enhance comprehension of sharia financial planning. The training was implemented by providing relevant materials and opportunities for hands-on practice. The effectiveness of the training was evaluated through the administration of pre-test and post-test questionnaires to each participant. The results demonstrated an average increase in each indicator of understanding of Perencanaan Keuangan Syariah, indicating that the training was successful. However, there is still a need to improve the financial literacy of the younger generation.